Rare Gingival Metastasis by Hepatocellular Carcinoma. (12th March 2017) - Xue, Li-Jun; Mao, Xiao-Bei; Geng, Jian; Chen, Ya-Nan; Wang, Qian; Chu, Xiao-Yuan
Abstract : Hepatocellular carcinoma (HCC) uncommonly metastasizes to the gingiva, which always means a poor outcome. We reported a rare HCC case with multiple metastases to gingiva, lungs, and brain. A 60-year-old man was initially diagnosed as HCC with metastases to double lungs. He was subjected to a transarterial chemoembolization (TACE) (5-fluorouracil, 750 mg) and two cycles of intravenous chemotherapy (gemcitabine 1.8 g at days 1 and 8, oxaliplatin 200 mg at day 2, every 4 weeks). However, the volume of liver tumor still increased. A bean-size gingival nodule growing with occasional bleeding was also found. TACE (5-fluorouracil 750 mg, perarubicin 40 mg, cisplatin 20 mg) was performed again and an oral sorafenib therapy (400 mg, twice per day) was adopted. The disease maintained relatively stable for about 6 months until a second obvious progress. The gingival nodule was then palliatively excised and identified as a poorly differentiated metastatic HCC by histopathological examination. Best supportive treatments were made since the performance score was too bad. Finally, cerebral metastases occurred and the patient died of systemic failure. Upon review of previous reports, we discussed risk factors, clinical and pathological characteristics, treatments, and prognosis of gingival metastasis by HCC.